Direct dotterising or angioplasty of acute stroke due to tandem atherosclerotic occlusions - Yeo, Leonard L. L.; Simonato, Davide; Bhogal, Pervinder; Gopinathan, Anil; Cunli, Yang; Ong, Samuel W. Q.; Jing, Mingxue; Tan, Benjamin Y. Q.; Sia, Ching-Hui; Jia, Tom; Cester, Giacomo; Gabrieli, Joseph-Domenico; et al. (Frontiers in Stroke, 2023)
Background: Tandem occlusions cause 10-15% of acute ischemic strokes but are complicated to treat endovascularly and frequently excluded from clinical trials. The optimum endovascular method is still debated, however directly going through the carotid occlusion can speed up the procedure and reduce procedural risk by eliminating an exchange maneuver. Results: Forty-two consecutive patients with atherosclerotic tandem occlusions were included, 25 were treated with the 0.014’wire technique and 17 with the 0.035’-guidewire and direct dotterisation or angioplasty with a peripheral vascular balloon technique. Successful recanalization was seen more frequently in the direct technique (100% vs 72%, P= 0.018), as well as better functional outcomes (88.4% vs 48.0%, P =0.044) and faster procedure times (mean 65.1 mins vs 114.8 mins, P<0.001). The number of attempts was similar between both groups (median 2 vs 3 attempts, P=0.101). There was no significant difference in the complication rate between both groups (5.9% vs 12.0%, P =0.462). Conclusion: Compared to previous endovascular techniques for treating atherosclerotic tandem occlusions, the direct technique using standard 0.035’ guidewires and dotterisation or a peripheral vascular balloon is significantly faster with better outcomes. However, this will need external validation in a larger series.